Dewan Redaksi Prosiding - Dewan Redaksi (Himpunan Sarjana-Kesusastraan Indonesia (HISKI), 2023)
Dewan Redaksi Prodising: THE 31st HISKI INTERNATIONAL CONFERENCE ON LITERARY LITERACY AND LOCAL WISDOMOrganizing CommitteeChairperson: Prof. Dr. Fransiskus Bustan, M.Lib.Secretary: Leni Amelia Suek,SS. MATreasurer/Consumption: Elisna Huan, S.Pd., M.HumPaper: Dewi I.N. Bili Bora, S.Pd., M.Ed and Gracia M. N. Otta, S.Pd., M.EdProgram: Ragil Afriansah YTransportation, Accommodation and Logistics: Salvator Candra DadusPublication and Documentation: Roni F. ManuReviewerProf. Dr. Fransiskus Bustan, M.Lib.Drs. Alexander H. Kabelen, MADr. Karolus Bidiman Jama, S.Pd., M.PdProf. Drs. Tans Feliks, M.Ed Ph.DKeynote Speaker:Mami Fujiwara, Ph.D (Yamaguchi University, Japan)Zalina Abdul Azis (Author and Researcher, Malaysia)Drs. Florindo Pereira, M.Si., Ph.D (Universidade Oriental Timor Lorosa'e, Timor-Leste)Dr. Suraiya Chapakiya (Fatoni University, Pattani, Thailand)Prof. Dr. Moh Karmin Baruadi, M.Hum (Universitas Negeri Gorontalo, Indonesia)Dr. Vinsensius Adi Gunawan, SVD (Anthropos Institut Philosophisch-Theologische Hochshule SVD Sankt Augustin, Germany)